Diana Al Hadid: Phantom Limb / A Young Person's Guide - Hadid, Diana Al (NYUAD Gallery, Abu Dhabi; Skira Editore, Italy, 2016)
User-engagement pack accompanying the exhibition Diana al-Hadid: Phantom Limb at the Art Gallery of NYUAD, curated by Maya Allison from March-May 2016.
English
Keywords: 22nd century; N4390-5098 Visual Arts. Exhibitions